The Way of Problem Solution in Learning of Thai Dance Performance in Higher Education Under The Covid-19 Outbreak Situation - Achayuthakan , Malinee (Journal of Fine and Applied Arts Khon Kaen University, 2022)
This article is an academic article that aims to find a solution to the problems of learning Thai dance skills at the higher Education level in the situation of the COVID-19 epidemic by interviewing teachers in the field 0f teaching Thai dance skills with at least one semester of online teaching experience from 8 higher education institutions. According to COVID-19 outbreak prevention measures, Higher Education institutions need to adapt instruction approaches so suddenly that instructors need to apply technology skills for solving the problems, thus all places become a safe learning room by online teaching: The instructors have to teach Thai dance skills to learners by demonstrating them the steps of dancing that is an individual training approach so that the learners are able to perform appropriately and beautifully according to the model. Thus, it is unpreventable that touching each other while individual teaching is needed, including while pair or group practices indeed. That is why the instructors have to find a solution of problem in learning skills of Thai Dance with a mixed-method, flexible online classroom, and a hybrid classroom. The study found that when online learning could not push the students’ potential perfectly, an online teaching training by the institute for the instructors is needed, planning consequences of instruction concisely and recording a short video with clear explanations for the learners in advanced, giving them opportunities to question immediately and questioning forms. While the instruction, the learners have to take formative tests and record themselves in the video assignments in order that the instructor is able to advise individually. Furthermore, the screen on the device should be large, the internet access of the device should be stable, and the place should be large enough to practice dancing without everything disrupts their learning. In the way of problem solution in learning Thai dance skills in such situation, the instructor should not expect for the perfection from online learning in order to decrease the tense. However, the instructor should pay attention and take much time to develop for effectiveness so that it can be adapted with distance education in the future.